Pengembangan Media Pembelajaran Berbasis Game Edukasi Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa pada Materi IPAS Kelas V Sekolah - Wahyu Basri Lestari; Sugiyono Ardjaka; Ahmad Yani (EduInovasi: Journal of Basic Educational Studies, 2026)
This research was motivated by the low critical thinking skills of fifth-grade students in the IPAS (Natural and Social Sciences) subject, a result of using conventional learning media that failed to capture student interest. The study aimed to produce valid, practical, and effective learning media to enhance students' critical thinking skills. It employed the Research and Development (R&D) method using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The subjects were fifth-grade elementary school students in Cluster III, Gondang District. Two schools were selected as samples: SD Negeri 1 Wonokromo for the small-scale trial and SD Negeri 2 Tiudan for the large-scale trial. Data were collected using expert validation instruments, pre-tests and post-tests, and student response questionnaires. The results indicated that the developed educational game-based learning media met the "highly valid" criteria, achieving scores of 91.6% from media experts and 92% from subject matter experts. In field trials, the media was deemed highly practical, with an average score of 82.91% in the small-scale trial and 84.96% in the large-scale trial. Furthermore, the media demonstrated an improvement in students' critical thinking skills, evidenced by the increase in scores between the pre-test and post-test. These findings indicate that the developed educational game-based learning media is effective for implementation in learning activities.